Turkish-Dutch bilinguals maintain language-specific reference tracking strategies in elicited narratives. (April 2020) - Azar, Zeynep; Özyürek, Aslı; Backus, Ad
Aim: This paper examines whether second-generation Turkish heritage speakers in the Netherlands follow language-specific patterns of reference tracking in Turkish and Dutch, focusing on discourse status and pragmatic contexts as factors that may modulate the choice of referring expressions (REs), that is, the noun phrase (NP), overt pronoun and null pronoun. Methodology: Two short silent videos were used to elicit narratives from 20 heritage speakers of Turkish, both in Turkish and in Dutch. Monolingual baseline data were collected from 20 monolingually raised speakers of Turkish in Turkey and 20 monolingually raised speakers of Dutch in the Netherlands. We also collected language background data from bilinguals with an extensive survey. Data and analysis: Using generalised logistic mixed-effect regression, we analysed the influence of discourse status and pragmatic context on the choice of subject REs in Turkish and Dutch, comparing bilingual data to the monolingual baseline in each language. Findings: Heritage speakers used overt versus null pronouns in Turkish and stressed versus reduced pronouns in Dutch in pragmatically appropriate contexts. There was, however, a slight increase in the proportions of overt pronouns as opposed to NPs in Turkish and as opposed to null pronouns in Dutch. We suggest an explanation based on the degree of entrenchment of differential RE types in relation to discourse status as the possible source of the increase. Originality: This paper provides data from an understudied language pair in the domain of reference tracking in language contact situations. Unlike several studies of pronouns in language contact, we do not find differences across monolingual and bilingual speakers with regard to pragmatic constraints on overt pronouns in the minority pro-drop language. Significance: Our findings highlight the importance of taking language proficiency and use into account while studying bilingualism and combining formal approaches to language use with usage-based approaches for a more complete understanding of bilingual language production.